Re: Andrea Necchi, Félix Guerrero-Ramos, Paul L. Crispen, et al. Gemcitabine Intravesical System plus Cetrelimab or Cetrelimab Alone as Neoadjuvant Therapy in Patients with MIBC: Primary Analysis and Biomarker Results of SunRISe-4. J Clin Oncol. In press. https://doi.org/10.1200/JCO-25-02382 - Giuseppe Di Lorenzo; Carlo Buonerba (European Urology Oncology, 2026)
In AEGEAN, perioperative durvalumab plus neoadjuvant chemotherapy, versus neoadjuvant chemotherapy alone, significantly improved event-free survival (EFS) and pathologic complete response in patients with resectable non-small cell lung cancer (R-NSCLC), with a safety profile consistent with the individual agents. We report EFS from a second planned interim analysis, interim disease-free survival (DFS) and overall survival (OS), and safety, after all patients completed/discontinued treatment. In this phase III, double-blind, placebo-controlled study, patients with treatment-naïve R-NSCLC (stage II-IIIB [N2]) were randomly assigned (1:1) to neoadjuvant platinum-based chemotherapy plus durvalumab/placebo (once every 3 weeks, four cycles) presurgery and then adjuvant durvalumab/placebo (once every 4 weeks, 12 cycles). Efficacy was analyzed in the modified intention-to-treat population (n = 740; for DFS, its resected subpopulation), which excluded patients with documented EGFR/ALK aberrations. As of May 10, 2024 (median follow-up, 25.9 months [censored patients]), EFS benefit favoring the durvalumab arm remained consistent (hazard ratio [HR], 0.69 [95% CI, 0.55 to 0.88]). Numerical improvement in DFS (HR, 0.66 [95% CI, 0.47 to 0.92]) and OS (HR, 0.89 [95% CI, 0.70 to 1.14]) favored the durvalumab arm. Maximum grade 3/4 adverse events occurred in 15.4% and 10.6% of the durvalumab and placebo arms, respectively, during adjuvant treatment. These results further support perioperative durvalumab plus neoadjuvant chemotherapy as a new treatment option.